The Effectiveness of Bladder Filling Technique for Preventing Intraoperative Bladder Injury in Pregnant Women Undergoing Placenta Accreta Surgery: A Systematic Review - Nawras Fashafsheh PhD; Ismail A Elhaty PhD (SAGE Open Nursing)
Background Placenta accreta spectrum (PAS) disorders have become more noticeable as a serious and potentially life-threatening obstetric concern due to a rise in prevalence from 0.12% to 0.31% in recent years. New preventive measures, such as the bladder filling technique, seek to identify the bladder's borders, protect it, and displace it away from the lower uterine segment during placental removal. Aim To determine whether the saline bladder filling technique prevents the incidence rate of intraoperative bladder injuries among pregnant women undergoing PAS surgery. Method Systematic searches were conducted in PubMed, Embase, and the Cumulative Index to Nursing, Allied Health Literature and, Google Scholar from 2013 to 2023. The Cochrane Risk of Bias (ROB 2.0) and ROB in Nonrandomized Studies of Interventions tools were used to assess the quality of the selected studies Findings A total of 2,094 articles were initially retrieved, and after screening, four articles met the eligibility criteria and were included in the final. The primary outcome of this systematic literature review (SLR) indicates that the utilization of the bladder filling technique was associated with a reduced occurrence of bladder injury, with an incidence range of 4.5% to 21.9% when the bladder filling technique utilized, in contrast to an incidence range of 13.1% to 32.4% when the bladder-filling technique was not utilized. Furthermore, the utilization of the bladder filling technique was found to be correlated with a reduced surgical procedure time and decreased blood loss. Conclusion This SLR reveals that utilizing the bladder filling technique during PAS surgeries decreases the occurrence of intraoperative bladder injury, which, in turn, reduces the occurrence of other intraoperative complications, including intraoperative blood loss. Therefore, healthcare providers and policymakers should start developing surgical protocols for the use of this technique, as it has the potential to significantly impact the outcomes of pregnant women undergoing PAS surgeries.